Conversion therapy with immunotherapy plus chemotherapy achieves a pathological complete response in stage IIIC NSCLC - Fu, Yu; Duan, Weichen; Xu, Ran; Chen, Jiajia (Frontiers in Immunology, 2023)
As stage IIIC non-small cell lung cancer (NSCLC) is not recommended for surgical resection, the survival and prognosis for stage IIIC NSCLC remain poor. More powerful and individualized therapies are urgently needed to improve the prognosis of stage IIIC NSCLC. Recently, immunotherapeutics have been increasingly considered in the neoadjuvant therapy of NSCLC. This study presents a patient with stage IIIC NSCLC achieving a pathological complete response (pCR) following conversion therapy with immunotherapy plus chemotherapy. This case also presents a histologic transformation from squamous cell carcinoma to adenocarcinoma after prolonged progression-free survival (PFS) following surgery. Collectively, this case suggests that conversion immunotherapy with chemotherapy and subsequent surgery can be considered and benefits a subset of unresectable stage IIIC NSCLC.